Pelayanan dalam Perusahaan Perspektif Islam - Suwarno (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
One of the factors contributing to the growth of a company lies in the services provided and the marketing strategies employed by the company. This research examines the topic of Service in a Company from an Islamic Perspective. Utilizing a literature review approach, the obtained data is qualitatively analyzed and then presented descriptively, outlining, depicting, and explaining in accordance with the issues closely related to this research. The research findings reveal that services should be conducted in accordance with Sharia principles. To ensure that services in a company from an Islamic perspective are more focused, especially in service-oriented companies, all parties involved must adhere to guidelines and principles set forth in Islamic teachings